Waterproof packing for urban outdoor : Development of two waterproof backpacks intended for daily bike commute, urban strolls and travel - Winnberg, Anton (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
Everyday, lots of people use some sort of bag to carry their daily equipment around, whether it is between home and work or any typ of spare time activity. This report covers a Master Thesis project in Industrial Design Engineering at Luleå University of Technology. The thesis concerns the development of two waterproof backpacks. These backpacks are developed in collaboration with the outdoor brand Lundhags, and intended for everyday bike commute, urban excursion and travel. Behind the initiative lies the desire of expanding the company’s product portfolio with a set of new waterproof daypacks within the category of urban outdoor. Also, to offer the customers the better protection of electronic devices such as laptops, surf tablets and smartphones, which are products that are prominent in our daily lives. The project has followed a schedule and workflow influenced by versions of the design thinking process, with multiple iterations along the way. The work started off by studying competing products on the market, research and conduct knowledge on relevant topics through a literature review, study users needs and gather inspiration. User studies where carried out as interviews with both users and retailers, where the result was summarised as personas to represent the target audience. The contextual studies laid the foundation for the rest of the project, which further shifted towards more practical activities. Such as ideation sketching, building textile and paper mock-ups, concept development and concept evaluation. The result of this thesis project was the first version technical drawings for two backpack concepts. During the final weeks, these drawings were sent to the manufacturer for production of first version prototypes and production cost proposal. The bags are planned as a 16 liter and a 22 liter, where they offer internal options of organising the packing, as well external access pockets for smaller items to be close at hand. Varje dag så använder massor av människor någon form av väska för att bära ...